Effect of human bone lyophilized graft and human lyophilized amniotic membrane on bone regeneration of rabbit tibias - Paredes Nomberto, Frank (2015)
This study aimed to investigate the effect of lyophilized human bone graft in combination with lyophilized human amniotic membrane in bone regeneration of rabbit tibias. Methodology: It were used 10 New Zealand male and female white rabbits 6 to 9 months of age, in good condition, weighing 3.5 kg-4 kg. Two circular bone defects 4mm diameter were created in the lower región of the tibias. One of the defects made belonged to control group and was only covered with amniotic membrane, the other defect belonged to the experimental group and was covered with lyophilized human graft plus lyophilized amniotic membrane as a barrier. The animals were sacrificed at 16 weeks after surgery and a clinical and histological analysis of the area of bone defects was done. It was concluded that bone regeneration was significantly higher in the defects covered with lyophilized human bone in combination with amniotic membrane than the control group which took only amniotic membrane as a barrier.